“BOOK SCIENCE”: THE CONTINUITY OF TRADITIONS AND THE IDENTITY - BRAZIŪNIENĖ, ALMA (Knygotyra, 2013)
The article deals with the analysis of the Vilnius University research papers “Knygotyra” (Book Science) in 1999–2012. The first volume of “Knygotyra” was published in 1961 under the title “Bibliotekininkystės ir bibliografijos klausimai” (Issues of Librarianship and Bibliography) which was changed to “Knygotyra” in 1970. Today, “Knygotyra” is a mature and recognised journal. It is edited by a team of international editors, which includes researchers from Estonia, Finland, Germany, Latvia, Poland, Russia and Lithuania. “Knygotyra” is the only journal of book science in Lithuania and in the Baltic countries. The state and situation of “Knygotyra” in 1970–1998 was analyzed by Vanda Stonienė (2000). The aim of the present article is to reveal the “Knygotyra” status in the recent years (1999–2012) and to compare it with the analysis by V. Stonienė. “Knygotyra” is analyzed in the organizational, structural, thematic, genre publications, authors’ activity and other aspects. The analysis concludes that "Knygotyra” keeps its traditions. On the other hand, a scientific journal is forced to change. It is influenced by the country’s general education policy trends, changes in the global world and scientific research field. One of the formal proofs of this change is the size of each annual volume, which has increased from 20 quires in 1999 to 44 in 2012. The reasons for this increase are complex: achievements of ancestors, attention to foreign authors, scientific communication (international conferences in Vilnius), scientific potential of the growing Lithuanian book community. Upon comparing the periods 1970–1998 and 1999–2012, we can state that the editorial bord of “Knygotyra” ensures a balanced preparation, reviewing and publishing of the material, and authoritative foreign scientists in the editorial bord increase the academic prestige of “Knygotyra”. After examining the structure and publications by genre and comparing it with the previous analysis by V. Stonienė, we can see that “Knygotyra” is trying to follow traditions to publish actual and problematic topics of book science. In total, 369 articles were analyzed. A comparative analysis revealed that the recent theme of peer-reviewed articles has expanded enormously. In 1970–1998 it was concentrated on the history of book and the history of libraries. We find that in 1999–2012 the focus of topics was also on traditional book history. This is evidenced by historiographic Lithuanian book science school. In 1999–2012, the number of articles on book theory and methodology increased. Usually, they are written not by Lithuanian authors, but this is one of the ways to fill a gap of these actual topics. A comparative analysis of the published articles revealed that new items such as bibliophilia, book art, handwritten and printed heritage have appeared in “Knygotyra”. Such topics as publishing were not popular in 1970–1998 (except the topics of publishing history), in 1999–2012 this topic has been one of the most actual and pressing. This is due to the fact that the Institute of Book Science and Documentation of Vilnius University is pursuing a bachelor’s degree and master’s degree programs on publishing. Two dissertations on publishing topics have been recently defended. All this shows that the today’s situation has influenced changes of “Knygotyra”: new topics of subjects reflecting the scientific relevance of book science (book advertising, digital book, book branding, etc.) have appeared in “Knygotyra”. The thematic distribution of articles also testifies to a much broader phenomenon – the general direction of the development of Lithuanian book science, research topics of the Institute of Book Science and Documentation, the future dissertation topics. All these things show that “Knygotyra” as a scientific journal has formed its own identity: it follows the publishing traditions, has its core authors, is recognized and appreciated not only in Lithuania, but also in foreign countries.